2006
DOI: 10.1186/cc5128
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory alterations induced by sedation in intensive care patients. Effects of midazolam alone and in association with sufentanil

Abstract: Introduction Sedation is widely used in intensive care unit (ICU) patients to limit the risk of pulmonary barotrauma and to decrease oxygen needs. However, adverse effects of sedation have not been fully evaluated; in particular, effects of benzodiazepine and opiates on microcirculation have not been extensively studied. The aim of this study was to evaluate the microcirculatory effects of a sedation protocol commonly prescribed in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The laser Doppler flowmeter probe was placed on the internal portion of the right thigh. Although precise quantifications cannot be made, it has been shown that changes in skin microcirculation can be monitored with this technique during sedation or anesthesia 15,16…”
Section: Methodsmentioning
confidence: 99%
“…The laser Doppler flowmeter probe was placed on the internal portion of the right thigh. Although precise quantifications cannot be made, it has been shown that changes in skin microcirculation can be monitored with this technique during sedation or anesthesia 15,16…”
Section: Methodsmentioning
confidence: 99%
“… 9 In the microcirculation, deep sedation induces deterioration in vasomotor function and response to ischaemia, suggesting sedation strategy could affect tissue perfusion at the microcirculatory level. 10 In the immune system, sedatives can inhibit neutrophil and macrophage function, decrease bacterial clearance and increase mortality in infected animals. 11–17 Significant to the paradigm of early deep sedation, these immunomodulatory effects can be seen early, within 1–2 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Univariate analysis also indicated a possible relationship between MARSI and prolonged sedation during their ICU stay. Sedation causes a decrease in blood pressure and an impaired vasomotion after the administration of the sedatives midazolam and sufentanil 18. However, the effects demonstrated in this were the result of short-term sedation and the relationship between prolonged sedation and MARSI risk is not known.…”
Section: Discussionmentioning
confidence: 93%